Adaptation of some energetic parameters during transition period in dairy cows. Issue 1 (1st January 2018) - Fiore, Enrico; Piccione, Giuseppe; Rizzo, Maria; Morgante, Massimo; Barberio, Antonio; Giudice, Elisabetta; Gianesella, Matteo
ABSTRACT: The aim of this study was to evaluate the effect of peripartum period and lactation class on serum β-hydroxybutyrate, non-esterified fatty acids (NEFA), insulin and glucose concentration in dairy cows. Thirty-five multiparous Holstein cows were selected from a high-producing dairy farm. The animals were divided according to their lactation class: second lactation group (L2, n  = 16), third lactation group (L3, n  = 10) and fourth lactation group (L4, n  = 9). Blood sampling were performed 7 ± 5 days before calving (Pre/C) and 7 ± 5 days after calving (Post/C). Two-way analysis of variance was applied to determine significant effects of lactation class (L2, L3 and L4) and period (Pre/C and Post/C) on studied parameters. Increased NEFA values and lower insulin levels were found in Post/C respect to Pre/C in L2 and L4. These changes highlight the difficulty of dairy cows to cope with the energy demand characterizing the transition period. Improving in knowledge of energetic metabolism changes may help to supply a new strategy of farm management and reproductive performance in dairy cows during the transition period.